Numerical DEM Analysis on Coal Loading Process of Shearer Spiral Drum - Tian, Zhen; Jing, Shuangxi; Gao, Shan; Zhao, Lijuan (Recent Patents on Mechanical Engineering, 2021)
Background: In order to study the loading process of shearer spiral drum, the theoretical model of loading process of spiral drum was established based on the kinematic characteristics of coal block in the envelope region of spiral drum. Objective: A spiral drum was designed for MG400/951-WD shearer, and this spiral drum was taken as the research object, the influence of spiral angle of the blade and rotation speed of the spiral drum on the theoretical coal capacity was analyzed. Methods: The intrinsic parameters of coal were calibrated according to the physical and mechanical properties of coal samples in Ordos Wenyu coal mine, a discrete element model of the coupling of the spiral drum and the coal wall was constructed. Results: The velocity and mass distribution of coal particles in the loading process were obtained by numerical simulation. The simulation results show that the loading rate of spiral drum was 65.6%. Through industrial test and theoretical calculation, the coal loading rate of spiral drum under the same conditions was 63% and 68.4%, and the maximum relative error between the results and theoretical calculation was 7.89%. Conclusion: The error between the coal loading rate obtained by the simulation, theoretical calculation and the test was small. It shows that the simulation results can accurately reflect the coal charging process of the spiral drum. In this article, various patents have discussed.
Keywords: spiral drum